The mistake occurs in Step 2. The student incorrectly combined the terms after distributing. The correct combination of terms in Step 2 should be:
Step 1: \( 2(x - 2) + 5x = 24 \) leads to \( 2x - 4 + 5x = 24 \).
In Step 2, the student incorrectly wrote this as \( 10x - 4 = 24 \), when it should actually be \( 7x - 4 = 24 \).
Thus, the mistake is in Step 2: the student should have added \( 2x + 5x = 7x \), not multiplied \( 2x \) and \( 5 \) to get \( 10x \).
So, the correct answer is: Step 2: The student should have added \( 2x + 5x = 7x \), not \( (2x)(5) = 10x \).